Advantages and Disadvantages of the Lithuanian Individual Constitutional Complaint Model - Pūraitė-Andrikienė, Dovilė (Teisė, 2020)
This article analyses the main elements of the model of individual constitutional complaint enshrined in the Constitution of the Republic of Lithuania and in the ordinary legislation. These elements are: objects of individual constitutional complaint; subjects entitled to lodge individual constitutional complaint and filters, which reduce the flow of individual constitutional complaints. This article aims to reveal the legal framework regulating these elements and to identify its advantages and disadvantages.
Keywords: individual constitutional complaint; Constitutional Court; constitutional justice model